The Influence of Psychological Well-Being, Work Discipline, and Organizational Culture on Job Satisfaction of Owabong Water Park Purbalingga Employees - Sa’roni, Imam Arief; Endratno, Hermin; Astuti, Herni Justiana; Arofah, Rifka Utami (Jurnal Ekonomi dan Bisnis Digital, 2025)
The objective of this study is to investigate the impact of Psychological Well-Being, Work Discipline, and Organizational Culture on Job Satisfaction of permanent employees of Owabong Water Park Purbalingga. These three factors act as independent variables, while Job Satisfaction is the dependent variable. This study involved the entire population of permanent employees of 101 people with a saturated sampling method, with analysis using multiple linear regression. The results of the study showed that Psychological Well-Being and Work Discipline had no effect on job satisfaction, whereas organizational culture had a considerable beneficial impact.